Comorbidities of overweight/obesity experienced in adolescence: longitudinal study. - Wake, M; Canterford, L; Patton, G; Hesketh, K; Hardy, P; Williams, J; Waters, E; Carlin, J (2010)
OBJECTIVES: Adolescent obesity is linked to metabolic and cardiovascular risk, but its associations with adolescents' experienced health and morbidity are less clear. Morbidities experienced by overweight/obese adolescents and associations between morbidities and timing of overweight/obesity were examined. METHODS: Data were from the Health of Young Victorians Study (HOYVS; 1997, 2000, 2005), a school-based longitudinal study. Outcomes were blood pressure, health status (Pediatric Quality of Life Inventory 4.0 (PedsQL), global health), mental health (Strengths and Difficulties Questionnaire), psychological distress (Kessler-10), physical symptoms, sleep, asthma, dieting, and healthcare needs and visits. Regression methods assessed associations with body mass index status and timing of overweight/obesity. RESULTS: Of the 923 adolescents (20.2% overweight, 6.1% obese), 63.5% were classified as "never" overweight/obese, 8.5% as "childhood only", 7.3% as "adolescence only" and 20.8% as "persistent". Compared to non-overweight, current obesity was associated with lower PedsQL physical summary scores (mean -6.58, 95% CI -9.52 to -3.63) and good/fair/poor global health (OR 3.52, 95% CI 1.95 to 6.36), hypertension (systolic 8.86, 95% CI 4.70 to 16.71; diastolic 5.29, 95% CI 2.74 to 10.20) and dieting (OR 5.79, 95% CI 3.28 to 10.23), with intermediate associations for overweight. Associations with psychosocial morbidity were weaker and inconsistent and there were few associations with health symptoms and problems. Only dieting (OR 2.30, 95% CI 1.36 to 3.89) was associated with resolved childhood overweight/obesity. CONCLUSIONS: Despite poorer overall health, overweight/obese adolescents were not more likely to report specific problems that might prompt health intervention. Morbidity was mainly associated with concurrent, rather than earlier, overweight/obesity.